Dynamic Interactions of Inelastic Structures and Fluids - W. Brunner; H. Irschik (Engineering Transactions, 1994)
A semi-analytic algorithm for the analysis of dynamie intera.ction between an elastoviscoplastic beam and the linear compressible fluid in a rectangular containment is presented. The inelastic parts of the strain in the beam are treated as unknown eigenstrains acting upon the linear elastic background structure. By means of this consistent eigenstrain analogy, the dynamic interaction problem is represented in a linear form. Using a substructure technique, dynamic influence functions for the eigenstrains are developed in the frequency domain and transformed back to the time domain, partly by analytic transformation, and partly by FFT. The eigenstrains are subsequently evaluated from the inelastic constitutive equations in a time stepping procedure, the influence functions being used, in connection with appropriate non-linear algorithms.